The legal regulationof digital currency and Bitcoinas amodel; comparativeanalyticalstudy - Mahmoud, Dalawar Saleh (Journal of Legal and Political Studies, 2025)
This study addresses the legal challenges arising from the rapid evolution of digital currenciesو emphasizing the need for both national and international legislative frameworks to regulate their use The research highlights the insufficiency of existing laws to govern digital currency transactions, underscoring the necessity for a regulatory environment that ensures the security and integrity of these transactions. The study employs an analytical methodology to examine various perspectives and legislations related to digital currencies, aiming to identify best practices. Additionally, a comparative methodology is used to contrast the laws of different countries. The study concludes with several key findings. Among these is the observation that the trading of digital currencies impacts monetary policy by influencing the expected volume of tax revenues if not strictly and legally regulated. This could impose additional obligations on companies, individuals, and financial institutions. The study also offers a number of recommendations, including the imperative to establish legislation that safeguards the rights of transaction parties on one hand, and enhances oversight of illegal digital activities on the other. Furthermore, the study recommends amendments to the Central Bank of Iraq's law. ‎ Keywords: Digital Currencies , EconomiC Ipacts , Legal Framework, Bitcoin
Keywords: Digital Currencies; EconomiC Ipacts; Legal Framework; Bitcoin